Analysis of the differences in green farming behavior of operating agents in grassland pastoral areas - Xue, Fang; Gao, Bo; Qiao, Guanghua; Wen, Lu (Frontiers in Environmental Science, 2023)
Green farming is the inevitable path to solving the problem of pasture ecological protection and a fundamental guarantee to realize the high-quality development of grassland animal husbandry. This paper explores the differences in green farming behaviours of different operating agents in grassland pastoral areas. The mechanism of the formation of the differences is based on 274 working agents' survey data from Xilin Gol league pastoral areas in Inner Mongolia, China, by constructing the Logit model and Fairlie decomposition method. The results show that family ranch is the primary operating agent of green farming in China's grassland pastoral areas. The green farming behaviour is 2.115 times more extreme than traditional pastoralists. Differences in the intensity of green farming behaviour of the operating agents were significantly and positively correlated with differences in their ecological consciousness and differences in resource endowment. Differences in ecological consciousness and participation in training were the key factors contributing to the differences in the intensity of green farming behaviours among the operators, with ecological consciousness contributing 51.34% and participation in training contributing 46.65% to the differences in the intensity of green farming behaviours. Therefore, to enhance the effective transformation of traditional pastoralists' green farming behaviour, we should guide them to raise ecological consciousness. And pay attention to the role of resource endowment and gradually form a new grassland animal husbandry development where green farming behaviour fully landed.